Enhancing antibacterial photodynamic therapy with NIR‐activated gold nanoclusters: Atomic‐precision size effect on reducing bacterial biofilm formation and virulence - Chengyu Liu; Tenghui Tian; Yujia Shi; Meiqi Li; Le Hong; Jing Zhou; Jia Liu; Yuan Zhong; Xue Wang; Zhenyu Wang; Xue Bai; Lin Wang; et al. (Aggregate)
Abstract Persistent biofilm infections pose a critical health threat with their relentless presence and amplified antibiotic resistance. Traditional antibacterial photodynamic therapy can inhibit bacteria extracellularly but struggles to control biofilm formation and virulence. Thus, there is an urgent need to develop photosensitizers, such as ultra‐small gold nanoclusters (AuNCs), that can penetrate biofilms and internalize into bacteria. However, AuNCs still face the challenge of insufficient reactive oxygen species (ROS) production and limited near‐infrared light absorption. This study develops a model of indocyanine green (ICG)‐sensitized AuNCs with atomic‐precision size effect. This approach achieved near‐infrared light absorption while inhibiting radiation transitions, thereby regulating the generation of ROS. Notably, different‐sized AuNCs (Au10NCs, Au15NCs, Au25NCs) yielded varied ROS types, resulting from different energy level distributions and electron transfer rates. ICG‐Au15NCs achieved a treatment efficacy of 99.94% against Staphylococcus aureus infections in vitro and significantly accelerated wound healing in vivo. Moreover, this study highlights the unique role of ICG‐AuNCs in suppressing quorum sensing, virulence, and ABC transporters compared to their larger counterparts. This strategy demonstrates that atomic‐precision size effect of AuNCs paves the way for innovative approaches in antibacterial photodynamic therapy for infection control.